The Effect of Company Growth and Liquidity on Company Value with Capital Structure as an Intervening Variable - Lydia Indah Permatasari; Yanuar Ramadhan (International Journal of Social Service and Research, 2023)
This study aims to obtain empirical evidence about the effect of company growth and liquidity on firm value, with capital structure as the intervening variable. The company's growth variable is measured using the percentage increase in the company's total sales, the difference between the company's total sales in this period and the previous period's total sales. The variable liquidity is measured by the current ratio, which is a measurement of the current assets owned by the company and the current liabilities of the company. The capital structure variable as an intervening variable is measured by the debt-to-equity ratio, which is the ratio between the total debt owned by the company and the capital owned by the company itself. The firm value variable as the dependent variable is measured based on the book value of the stock price, namely the stock price compared to the book value per share. The population in this study used 24 coal sub-sector mining companies listed on the IDX for the 2018–2022 period. The sample was selected using a purposive sampling method. The researcher obtained a sample of 11 companies in the coal mining sub-sector. The results of this study found that while company growth has no effect on capital structure, liquidity has a negative effect on capital structure. Company growth, liquidity, and capital structure have no effect on firm value. The capital structure is unable to mediate the relationship between company growth and liquidity and firm value.